Efektivitas latihan lompat gawang pada kemampuan tendangan mawashi geri dalam seni bela diri karate - Tri Wulandari, Nadia; Sujarwo, Sujarwo (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
Improving the ability to kick mawashi geri in karate martial arts requires measured and planned training, namely through hurdle jump training, which is specific to karate martial arts. This research aims to determine the effectiveness of hurdle jump training on the ability to kick mawashi geri in karate martial arts. The research uses quantitative methods with a pre-experimental design through a one-group pre-test post-test design. The sample in this study consisted of 25 students who actively carried out extracurricular activities at Senior High Schools in Southeast Sulawesi Province. The instrument used to measure mawashi geri kick ability in karate martial arts is using mawashi geri kicks for 30 seconds. The training used to improve mawashi geri kicking ability in karate martial arts is using plyometric hurdle jump exercises with low and high jump sequences. The data analysis technique uses quantitative data analysis with probability statistics, using prerequisite data analysis tests with normality and homogeneity tests followed by the t-test at a significance level of 0.05 using SPSS version 26. From the results of the pre-test and post-test data analysis, Mawashi Geri's kicking ability through hurdle jump training has a significance of 0.000 < 0.05, meaning that there is a significant influence between the pre-test and post-test variables on the ability to kick Mawashi Geri in karate martial arts sports. Hurdle jump training can help athletes integrate the strength and control they gain from hurdle jump training in the context of the mawashi geri technique.